2009
DOI: 10.1038/sc.2009.90
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction, appraisals and functional outcomes in spinal cord-injured people living in the community

Abstract: Study design: Multi-centre, single cohort. Objectives: To assess the relationship between cognitive appraisals in a spinal cord-injured population living in the community, and examine how these factors affect social participation, life satisfaction and functional outcomes. Setting: The National Spinal Injuries Centre, Stoke Mandeville, UK; Princess Royal Spinal Injuries Centre, Sheffield UK; Midlands Centre for Spinal Injuries, Oswestry, UK. Method: Participants (n ¼ 81) sustaining injury aged 18 or above were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 16 publications
4
40
0
Order By: Relevance
“…39 The passive and disengaged coping strategy 'social reliance' was found to be significant in explaining the variance in these outcome measures. Clinically, if patients are assessed using these measures prior to commencing active rehabilitation, those tending to see their injury as a loss or those patients prone to using passive and avoidant behavioural strategies to deal with the emotional sequelae of their injury could receive additional support, psycho-education or participate in Coping Effectiveness Training.…”
Section: Discussionmentioning
confidence: 88%
“…39 The passive and disengaged coping strategy 'social reliance' was found to be significant in explaining the variance in these outcome measures. Clinically, if patients are assessed using these measures prior to commencing active rehabilitation, those tending to see their injury as a loss or those patients prone to using passive and avoidant behavioural strategies to deal with the emotional sequelae of their injury could receive additional support, psycho-education or participate in Coping Effectiveness Training.…”
Section: Discussionmentioning
confidence: 88%
“…Perceived manageability (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Across the whole sample, there was a significant increase in scores for perceived manageability t(200) ¼ À2.831, P ¼ 0.005.…”
Section: Appraisal Of Life Events (Ale Subscalesmentioning
confidence: 99%
“…In relation to people with SCI, not only have appraisals been indicated in long-term psychological adjustment 15 but also in terms of functional outcome measures. Using the Appraisals of Disability: Primary and Secondary Scale, 16 Kennedy et al 17 found appraisals to explain 49.4% of the variance of Functional Independence Measure (FIM) scores. The current research builds on findings from an earlier cohort study that investigated appraisals, coping and QOL across four community samples.…”
Section: Introductionmentioning
confidence: 99%
“…33,34,37,56,57 Overwhelming disbelief, fearful despondency and negative perceptions of one's disability were associated with lower life satisfaction, 56 whereas growth and resilience were associated with greater life satisfaction. 56,57 The appraisals threat, challenge and loss have been employed in two studies. 33,34 Moreover, one study examined the appraisals threat, challenge and control.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…The way in which an individual thinks about or 'appraises' a situation 33 Appraisal of Life Events (ALE); 33,34 The Pakenham scale; 37 APAPSS Scale; 56 Illness Cognition Questionnaire (ICQ) 57 Higher order cognitive processes and an evaluation on the availability of coping resources, their sufficiency in the current environment and the likelihood that they can be used in the current situation (Galvin and Godfrey, 2001) 56 anxiety. 33,34,37 Loss appraisals were associated with lower life satisfaction, and higher levels of depression and anxiety.…”
Section: Appraisalsmentioning
confidence: 99%